The Consequences of Civil-Military Relations on Civil Wars in the Middle East - Bahnasy, Alaa (AUC Knowledge Fountain, 2024)
To unravel the complex dynamics surrounding the outbreak of civil wars in the aftermath of the Arab Spring uprisings, one of the first questions that come to mind is the reason why some Arab countries have witnessed civil wars whilst others have not. The civil-military relations play a significant role in the matter. While much of the existing literature on the causes of civil wars, there is a scarcity of papers that take into consideration the role of civil-military relations. This research focuses primarily on two variables independent variables, namely the civil-military relations and the diversified ethnicities alongside the dependent variable of civil wars. Understanding the regimes at work is vital to comprehend the causes of civil wars and how certain regimes have managed to suppress them while others have fallen into years-long civil wars.